Principal's Strategic Analysis in Mitigating BOS Fund Disbursement Delays Based on Low-Cost High-Impact Principles: A Case Study at SMPIT Harapan Ummat Purbalingga - Anta Ibnu Marzuq Arum; Faqih Tsabitul Azmi; Ahmad Fathur Ripqi; Sudiro Sudiro (STKIP Subang, 2026)
The delay in the disbursement of School Operational Assistance (BOS) funds is a recurring structural problem that disrupts school financial management. This study aims to analyze the strategies employed by the school principal to mitigate the risks of BOS fund disbursement delays based on the Low-Cost High Impact (LCHI) prin-ciple at SMPIT Harapan Ummat Purbalingga. This research employed a qualitative approach with a single case study design (Yin, 2018). Data were collected from May 1–22, 2026 through in-depth semi-structured interviews with seven informants (school principal, vice principals, treasurer, administrative staff, senior teacher, and school committee chairperson), complemented by non-participant observation and document analysis. Data analysis followed the interactive model of Miles, Huber-man, and Saldana (2014). The results showed that the school principal implement-ed four main strategies: (1) internal cash reserve management (SILPA) as emer-gency bridging funds; (2) priority-based activity management through activity redis-tribution across months to avoid concentration in high-risk disbursement periods; (3) digital administration optimization via ARKAS to streamline reporting; and (4) inter-institutional networking with the Education Office and school principal forums (MKKS). These strategies were proven effective in maintaining operational continui-ty with minimal additional costs. Key indicators of success include: salary delays limited to a maximum of one week (occurring only once), no teacher turnover, no complaints from parents, and sustained educational service quality throughout dis-bursement delay periods. Keywords: BOS Fund, Disbursement Risk Mitigation, Low-Cost High Impact, School Principal Strategy, Islamic School Financial Management